Bidirectional Effects of Pyrrolidine Dithiocarbamate on Severe Acute Pancreatitis in a Rat Model - Huan Yang; ShuCan Ma; Yu Guo; DongLai Cui; JinFeng Yao (SAGE Publishing, 2019)
Introduction: The mechanism by which intestinal mucosal barrier is damaged in severe acute pancreatitis (SAP)-associated impairment is not fully understood. Methods: We established an l -arginine-induced SAP rat model, pretreated with or without pyrrolidine dithiocarbamate (PDTC). Hematoxylin and eosin staining was performed to evaluate the pathological alterations. Western blotting was conducted to detect the expression of autophagy-related proteins. Oxidative stress was assessed by the levels of malondialdehyde and superoxide dismutase. Results: We found significant injury of the intestinal mucosal barrier in SAP rats, with overexpression of Beclin-1, LC3, and p65. Pyrrolidine dithiocarbamate showed a bidirectional effect in protecting SAP rats. A high dose of PDTC aggravated disease in rats, while a low or medium dose of PDTC pretreatment, was able to alleviate tissue damage. Pyrrolidine dithiocarbamate changed the expression of Beclin-1, LC3, and p65 in the intestines. The fatty acid-binding protein level was increased in SAP rats with high-dose PDTC or without PDTC pretreatment and was reduced in SAP rats with low- or medium-dose PDTC exposure. Conclusions: Autophagy is involved in the impairment of intestinal mucosal barrier during SAP. A suitable dose of PDTC (1 or 10 mg/kg) may decrease the severity of SAP by inhibiting autophagy in intestinal mucosal cells.